2013
DOI: 10.1111/lam.12037
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal properties of durancins isolated from Enterococcus durans A5-11 and of its synthetic fragments

Abstract: Significance and Impact of the Study: Antifungal properties of durancins isolated from Enterococcus durans A5-11 and of their chemically synthesized fragments were determined. Treatment of D. hansenii LMSA2.11.003 strain with 2 mmol l À1 of the synthetic peptides led to the loss of the membrane integrity and to several changes in the ultra-structure of the yeast cells. This work contributes to improve understanding of molecular causes of antimicrobial activities of bacteriocins and their fragments. It may be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…durans KF65 was observed although previously it was reported that Ent. durans A5–11 was effective for the inhibition of fungal growth (Belguesmia et al ) showing that strain‐specific properties could play roles for antifungal functions. Another important observation was the fact that kefir isolates were less effective against A. niger compared to the other fungi tested in this study which was also observed for other Lactobacilli previously (Hassan and Bullerman ; Demirbaş et al ).…”
Section: Resultsmentioning
confidence: 99%
“…durans KF65 was observed although previously it was reported that Ent. durans A5–11 was effective for the inhibition of fungal growth (Belguesmia et al ) showing that strain‐specific properties could play roles for antifungal functions. Another important observation was the fact that kefir isolates were less effective against A. niger compared to the other fungi tested in this study which was also observed for other Lactobacilli previously (Hassan and Bullerman ; Demirbaş et al ).…”
Section: Resultsmentioning
confidence: 99%
“…In this trend, the number of reports concerning bacteriocins as antiprotozoal agents (20)(21)(22)(23) is surprisingly lower than that of reports aiming at other eukaryotic targets such as fungi (24)(25)(26) or even tumoral cells (27)(28)(29).…”
mentioning
confidence: 77%
“…As a class, AMPs are a conserved defense mechanism across most eukaryotic species (7). Indeed, organisms as genetically diverse as snails and humans both generate AMPs to limit growth of pathogenic microorganisms, including fungi (8)(9)(10)(11). Several mechanisms of action have been proposed for these molecules, and current findings suggest that many of them have more than one antimicrobial target at the cellular level (12,13).…”
mentioning
confidence: 99%